A sounding monument: how a new organ became old. Issue 1 (2nd January 2016) - Peters, Peter; Cressman, Darryl
Abstract: In 2012, a new pipe organ was unveiled in Amsterdam. This organ, the Van Straten organ, was designed and built as a replica of an organ originally built in 1479 by Peter Gerritsz. In this paper, we examine how the Gerritsz organ became the Van Straten organ by examining how contemporary organ builders were able to translate aspects of the original wind chest, pipes and keyboard into the new organ. By contextualising the meaning of the Van Straten organ within the Early Music movement and the desire for historically authentic instruments, we argue that the Van Straten organ is not simply a replica of a fifteenth-century organ, but rather an object through which knowledge about fifteenth-century musical culture is produced for twenty-first-century musicians, composers, researchers and listeners.